2017
DOI: 10.1002/jbio.201700211
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence and confocal microscopy for ex‐vivo diagnosis of melanocytic and non‐melanocytic skin tumors: A pilot study

Abstract: The use of fluorescent-labeled antibodies in ex-vivo CLSM is possible and could improve intraoperative diagnostics of skin tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 40 publications
0
51
0
4
Order By: Relevance
“…In order to maintain its high standards, each step of the process should be as simple and clear as possible not only to experts, but also to novice Mohs fellows. Fast acquisition and evaluation of the tissue samples are the most important advantages of ex vivo CLSM . Previously it has been shown that in contrast to the traditional processing of Mohs frozen sections, ex vivo CLSM is less labor intensive, less time consuming, and less expensive .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to maintain its high standards, each step of the process should be as simple and clear as possible not only to experts, but also to novice Mohs fellows. Fast acquisition and evaluation of the tissue samples are the most important advantages of ex vivo CLSM . Previously it has been shown that in contrast to the traditional processing of Mohs frozen sections, ex vivo CLSM is less labor intensive, less time consuming, and less expensive .…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition time of Vivascope 2500 is less than 7 minutes. The device together with the examination steps have also been described in previously published studies by the working group .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations